Selective Vitamin D Receptor Activation as Anti-Inflammatory Target in Chronic Kidney Disease. (6th January 2014) - Donate-Correa, J.; Domínguez-Pimentel, V.; Méndez-Pérez, M. L.; Muros-de-Fuentes, M.; Mora-Fernández, C.; Martín-Núñez, E.; Cazaña-Pérez, V.; Navarro-González, J. F.
Abstract : Paricalcitol, a selective vitamin D receptor (VDR) activator used for treatment of secondary hyperparathyroidism in chronic kidney disease (CKD), has been associated with survival advantages, suggesting that this drug, beyond its ability to suppress parathyroid hormone, may have additional beneficial actions. In this prospective, nonrandomised, open-label, proof-of-concept study, we evaluated the hypothesis that selective vitamin D receptor activation with paricalcitol is an effective target to modulate inflammation in CKD patients. Eight patients with an estimated glomerular filtration rate between 15 and 44 mL/min/1.73 m 2 and an intact parathyroid hormone (PTH) level higher than 110 pg/mL received oral paricalcitol (1 μ g/48 hours) as therapy for secondary hyperparathyroidism. Nine patients matched by age, sex, and stage of CKD, but a PTH level <110 pg/mL, were enrolled as a control group. Our results show that five months of paricalcitol administration were associated with a reduction in serum concentrations of hs-CRP (13.9%, P < 0.01 ), TNF- α (11.9%, P = 0.01 ), and IL-6 (7%, P < 0.05 ), with a nonsignificant increase of IL-10 by 16%. In addition, mRNA expression levels of the TNF α and IL-6 genes in peripheral blood mononuclear cells decreased significantly by 30.8% (P = 0.01 ) and 35.4% (P = 0.01 ), respectively. In conclusion, selective VDR activation is an effective target to modulate inflammation in CKD.